POTENSI PAJAK HOTEL DI KOTA GORONTALO - Sardjono, Olivia Y. M.; Ilat, Ventje; Warongan, Jessy D. L. (Universitas Sam Ratulangi, 2021)
Optimization of PAD resources needs to be done to improve the ability of the region to support the implementation of regional autonomy. Hotel Tax is a tax that has the potential to develop the tourism sector in Gorontalo City. The problem in this study is that the largest source of Gorontalo city revenue from 2015-2019 still comes from the Balance Fund post which shows the level of dependency on central funds is still high. For this reason, the writer is interested in researching about the